British monetary policy, 1924-1931: the Norman conquest of $4.86 - Moggridge, D. E. (Cambridge [Eng.] : University Press, 1972)
This book contains the study carried out to examine British's inter-war gold standard experience and the financial polices adopted within the period to address balance of payments challenges.
Includes index
Bibliography: p. 281-292.
usc 20/09/18
Loans
Keywords: Monetary policy; Gold standard; Great Britain